PENGARUH DIAMETER NOZZLE TERHADAP DIAMETER GEL PADA PROSES GELASI EKSTERNAL KERNEL CERIA STABILIZED ZIRCONIA (CSZ) - Nurwidyaningrum, Kristanti; Sediawan, Wahyudi Budi; Perdana, Indra (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
In the production of coated particles that meet the requirements for high temperature gas reactor fuels, one of quality control requirements for the kernel is diameter control. The study was conducted by varying the diameter of the nozzle for predicting the size of gel diameter obtained from external gelation process by correlating variables of feed density, feed viscosity, feed solution tension and nozzle diameter quantitatively with dimensional analysis method in the form of dimensionless numbers. Fabrication of CSZ kernel was done by preparing the feed solution, which consists of a mixture of ZrO(NO3)2.2H2O and Ce(NO3)3.6H2O, urea, tetrahydrofurfuryl alcohol (THFA) and poly vinyl alcohol (PVA). External gelation is performed by dripping sol feed solution through a nozzle into gelation column containing ammonium hydroxide solution to form CSZ gel. Droplet formation occurs when the feed solution passes by the nozzle. The diameter of the gel formed can be calculated by correlating nozzle diameter and physical properties of the feed solution using dimensional analysis. Gel diameter of the experimental results was measured using an optical microscope. The diameter of the gel obtained from the dimensionless number equation shows results that are not too different from the diameter of the experimental gel with some deviations in the data. Data of diameter measurement of experimental gel and data of calculation by dimensionless equation show that diameter of the nozzle is directly proportional to diameter of the obtained gel.